Space for self-expression: communication of Czech female athletes on social media and fansʼ reactions - Kateřina Turková; Veronika Macková; Alice Němcová Tejkalová (Karolinum Press, 2021)
Social media platforms allow athletes to share information with the public. This opportunity is arguably more important for female athletes who traditionally receive less space in the mainstream media than their male counterparts. This article focuses on the social media self-presentation of six successful, internationally recognized, professional Czech female athletes and their fans' reactions. By using qualitative and quantitative content analyses, it was revealed that throughout the season, the selected athletes presented themselves as powerful professionals, while their off-season posting tended to be more personal and, for the most part, more feminine. Contrary to previous research, fans did not frequently respond with explicitly sexual or negative comments. Moreover, they supported and admired the athletes, and in most cases, reacted positively. A higher sensitivity was indicated in relation to the sportswomen's personal relationships and opinions. This leads us to the conclusion that social media enables professional female athletes to present themselves more freely than traditional media and be positively received by the public.